2020
DOI: 10.3389/fgene.2020.554833
|View full text |Cite
|
Sign up to set email alerts
|

Drug Response Associated With and Prognostic lncRNAs Mediated by DNA Methylation and Transcription Factors in Colon Cancer

Abstract: Colon cancer is the most commonly diagnosed malignancy and the leading cause of cancer deaths worldwide. As well as lifestyle, genetic and epigenetic changes are key factors that influence the risk of colon cancer. However, the impact of epigenetic alterations in non-coding RNAs and their consequences in colon cancer have not been fully characterized. We detected differential methylation sites (DMSs) in long non-coding RNA (lncRNA) promoters and identified lncRNA expression quantitative trait methylations (lnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In a report by Zhang et al [18], LINC00460 showed significant hypomethylation in colorectal cancer tissue samples in comparison with adjacent noncancerous tissue specimens, which had a negative correlation with its expression. In addition, treatment with 5-aza-2'-deoxycytidine resulted in LINC00460 overexpression and demethylation in LOVO and SW620 cells, demonstrating that LINC00460 could be activated by DNA methylation.…”
Section: Regulation Of Linc00460 In Cancermentioning
confidence: 91%
See 2 more Smart Citations
“…In a report by Zhang et al [18], LINC00460 showed significant hypomethylation in colorectal cancer tissue samples in comparison with adjacent noncancerous tissue specimens, which had a negative correlation with its expression. In addition, treatment with 5-aza-2'-deoxycytidine resulted in LINC00460 overexpression and demethylation in LOVO and SW620 cells, demonstrating that LINC00460 could be activated by DNA methylation.…”
Section: Regulation Of Linc00460 In Cancermentioning
confidence: 91%
“…LINC00460 is generally upregulated in multiple tumor cells in comparison to that in control cells (Table 1), including bladder [13,14], breast [15], cervical [16,17], colon [18,19], colorectal [10,[20][21][22][23][24], esophageal [25], gastric [26,27], ovarian [28], lung [11,[29][30][31], pancreatic [32] and papillary thyroid cancers [33][34][35], as well as acute myeloid leukemia (AML) [36], glioma [37], head and neck squamous cell carcinoma (HNSCC) [38][39][40][41][42], hepatocellular carcinoma [43][44][45], laryngeal squamous cell carcinoma [46], meningioma [47], nasopharyngeal carcinoma [48] and osteosarcoma [49]. In addition, LINC00460 is also overexpressed in these tumor tissues compared with adjacent normal tissues.…”
Section: Linc00460 Expression In Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Analysis of genome-wide, sitespecific methylation data has helped elucidate much about cancer, especially about carcinogenesis, 17,18 molecular characterization, [19][20][21] and molecular indicators of prognosis, [21][22][23] but so far, methylation studies on cancer drug efficacy have been limited in scope, for example, focusing on a single cancer. 24,25 As of yet, there have been no systematic efforts to identify drug-methylation interactions in most cancers despite mounting evidence that methylation often plays a key role in the development of cancer drug resistance. [26][27][28] The Cancer Genome Atlas (TCGA) has collected tumor samples from a wide range of cancers for molecular characterization.…”
Section: Introductionmentioning
confidence: 99%